PENGARUH POLA ASUH ORANG TUA TERHADAP PEMBENTUKAN AKHLAK PRIBADI SISWA SMPN 2 GONDANGREJO KARANGANYAR - Tuzaroh, Fatimah; Dewanti, Erisa Nada; Lessy, Zulkipli (Atta'dib Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyse the effect of parental parenting on adolescent morals, especially morals towards oneself, in students of SMPN 2 Gondangrejo Karanganyar. Using mixed method sequential explanatory method, this research combines quantitative and qualitative approaches. Data were collected through questionnaires distributed to 35 randomly selected samples. Simple linear regression analysis was used to measure the influence of parenting patterns on student morals. The results showed that parenting patterns had a significant effect on students' morals towards themselves, with a contribution of 40.5%. Democratic parenting tends to produce very good and good morals, while authoritarian parenting tends to produce poor morals. Permissive parenting shows varying results. This study concludes that parenting has an important role in shaping adolescent morals, especially in the context of morals towards oneself.